The power of partnership seven relationships that will change your life - Riane Eisler (Novato, Calif New World Library, 2002)
The adventure of change -- Your relationship with yourself : body, mind, and spirit -- Your intimate relations : the heart of the matter -- Your work and community relationships : the widening circle of caring -- Your relationship with your national community : why politics matter -- Your relationship with the international community : the world around us -- Your relationship with nature : from mother earth to biotechnology -- Your spiritual relations : putting love into action -- Partnership living : it begins with you.
Includes bibliographical references and index
Keywords: Interpersonal relations